2021
DOI: 10.1108/wje-07-2020-0270
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic activity of CoFe1.9Mo0.1O4-Ce0.8Gd0.18Ca0.02O2-δcomposite cathode for ammonia synthesis from water and nitrogen

Abstract: Purpose This paper aims to investigate the electrocatalytic activity of CoFe1.9Mo0.1O4-Ce0.8Gd0.18Ca0.02O2-δ composite (CFMo-CGDC) for the direct synthesis of ammonia from H2O and N2 under atmospheric pressure. Designs CoFe1.9Mo0.1O4 nanoparticles (CFMo NPs) were synthesized via a sol-gel method. CFMo NPs were characterized using X-ray diffraction (XRD), Brunauer–Emmet–Teller (BET) specific surface area measurement and scanning electron microscope (SEM). Double-chamber reactor was used to synthesize ammonia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…When the applied voltage was further increased above 1.4 V, the ammonia production rate decreased significantly and reached its lowest value of 1.0×10 -11 mol s -1 cm -2 at 1.8 V, corresponding to a current density of 8.68 mA cm -2 and a Faradaic efficiency of 0.03 %. Low ammonia formation rates with corresponding low Faradaic efficiencies at higher voltages indicate that more than one process occurs at the cathode, and hydrogen evolution might be the predominant [26,49,54]. The formation rate of ammonia achieved using LBFCu is still higher than that reported using a Ru-based catalyst and water and nitrogen as precursors to synthesise ammonia (3.75 ×10 -13 mol s -1 cm -2 at 650 °C) [25].…”
Section: Synthesis Of Ammonia At Different Applied Voltagesmentioning
confidence: 87%
See 1 more Smart Citation
“…When the applied voltage was further increased above 1.4 V, the ammonia production rate decreased significantly and reached its lowest value of 1.0×10 -11 mol s -1 cm -2 at 1.8 V, corresponding to a current density of 8.68 mA cm -2 and a Faradaic efficiency of 0.03 %. Low ammonia formation rates with corresponding low Faradaic efficiencies at higher voltages indicate that more than one process occurs at the cathode, and hydrogen evolution might be the predominant [26,49,54]. The formation rate of ammonia achieved using LBFCu is still higher than that reported using a Ru-based catalyst and water and nitrogen as precursors to synthesise ammonia (3.75 ×10 -13 mol s -1 cm -2 at 650 °C) [25].…”
Section: Synthesis Of Ammonia At Different Applied Voltagesmentioning
confidence: 87%
“…Ammonia synthesis directly from H2O and N2 will bypass the hydrogen production stage, which can help reduce the carbon emission in H2 production when fossil fuel is used as energy resources [24]. It has been demonstrated that ammonia can be synthesised from H2O and N2 in electrolytic cells based on proton (H + ) or oxygen ion (O 2− ) conducting electrolytes and different working electrodes (cathodes) [25][26][27][28]. The principle of the electrochemical synthesis of ammonia from H2O and N2 using oxygen-ion, and conducting electrolytes is presented in eqs.…”
Section: Introductionmentioning
confidence: 99%